Retrosigmoid endoscopic keyhole for vestibular schwannomas: Systematic review and meta-analysis - Ernesto Enrique Horta-Tamayo; Diana Rosa Ortega-Raez; Lary Benice RodrÃguez Santillan; Luis CÃ©sar Acosta GonzÃ¡lez; Martha SuÃ¡rez RodrÃguez; Arminda GonzÃ¡lez GonzÃ¡lez (Revista Cubana de Medicina Militar)
Introduction: The development of endoscopy for vestibular schwannomas in recent decades offers a panoramic view of the structures of this location that is superior to microscopic vision. Objective: To specify role of the retrosigmoid endoscopic keyhole in vestibular schwannomas. Method: The search was developed in Medline. The following terms in English with Boolean operators were used: "Vestibular schwannoma" OR "acoustic neurinoma" AND "keyhole approach" OR "endoscopic resection" OR "endoscopy". Spanish and English language restriction was used. Editorial articles, letters to the editor, books, single case presentations, reviews, meta-analyses, and those with poor method were excluded; also articles on anatomical specimens. The Major package of the Jamovi software was used to perform a single-arm meta-analysis of total resection and "acceptable" post-surgical facial function, and estimate the overall effect. I 2 greater than 75 % was taken as high heterogeneity. Results: Eight articles were chosen for the study. In the analysis of total resection, it is estimated at 0.84 for a p-value less than 0.01. It was similar in the case of preservation of "acceptable" facial function, with 0.77. In a subgroup analysis, those series where the diameters of the tumor lesion were greater than 3 cm showed less preservation of facial function. The anatomical preservation of the facial nerve was less than 90 % in two series. Conclusions: The retrosigmoid endoscopic keyhole is an effective and safe technique in vestibular schwannomas. Studies in this regard reveal relative success, with acceptable rates of anatomical and functional preservation of the facial nerve.